Montelukast Prevents Mice Against Acetaminophen-Induced Liver Injury - Pu, Shiyun; Liu, Qinhui; Li, Yanping; Li, Rui; Wu, Tong; Zhang, Zijing; Huang, Cuiyuan; Yang, Xuping; He, Jinhan (Frontiers in Pharmacology, 2019)
Acetaminophen (APAP) is a widely used over-the-counter antipyretic and analgesic drug. Overdose of APAP is the leading cause of hospital admission for acute liver failure. Montelukast is an antagonist of cysteinyl leukotriene receptor 1 (Cysltr1), which protects from inflammation and oxidative stress. However, the function of montelukast in APAP-induced hepatotoxicity remains unknown. In this study, we examined whether pharmacological inhibition of Cystlr1 could protect mice against APAP-induced hepatic damage. We found that APAP treatment upregulated messenger RNA and protein levels of Cysltr1 both in vitro and in vivo. Pharmacological inhibition of Cysltr1 by montelukast ameliorated APAP-induced acute liver failure. The hepatoprotective effect of montelukast was associated with upregulation of hepatic glutathione/glutathione disulfide level, reduction in c-Jun-NH2-terminal kinase activation and oxidative stress. In mouse primary hepatocytes, inhibition of Cysltr1 by montelukast ameliorated the expression of inflammatory-related genes and APAP-induced cytotoxicity. We conclude that montelukast may be used to treat APAP-induced acute hepatic injury.